2006
DOI: 10.1111/j.1525-1438.2006.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Epithelioid trophoblastic tumor: a case report

Abstract: Epithelioid trophoblastic tumor is a rare and distinctive pathologic entity within the complex family of gestational trophoblastic disease. We describe a case of epithelioid trophoblastic tumor occurring in a 34-year-old woman, who presented with a large uterine tumor 3 years following an uncomplicated pregnancy. The clinicopathologic findings in this case are typical of this unusual entity and consistent with current literature, with the exception of negative beta-human chorionic gonadotrophin levels. The dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“… 8 Lo et al reported a 9-cm ETT extending to the right pelvic side wall, with an extensive area containing necrotic matter. 9 Liang et al, Noh et al, and Fadare et al have reported four cases of large cystic lesions containing hemorrhagic material and necrosis, as in this case, and some of their cases had fistulas in the uterine cavity. 6 , 10 , 11 In the present case, the fistula was narrow and was associated with no inflammation or foreign body reaction along its length; an inflow of menstrual blood through it was therefore considered unlikely.…”
Section: Discussionmentioning
confidence: 51%
“… 8 Lo et al reported a 9-cm ETT extending to the right pelvic side wall, with an extensive area containing necrotic matter. 9 Liang et al, Noh et al, and Fadare et al have reported four cases of large cystic lesions containing hemorrhagic material and necrosis, as in this case, and some of their cases had fistulas in the uterine cavity. 6 , 10 , 11 In the present case, the fistula was narrow and was associated with no inflammation or foreign body reaction along its length; an inflow of menstrual blood through it was therefore considered unlikely.…”
Section: Discussionmentioning
confidence: 51%
“…The well-circumscribed, nodular growth pattern of ETT is not seen in CC. The hyaline like matrix and necrosis present in ETT can resemble keratin and has reportedly lead to the misdiagnosis of cervical squamous cell carcinoma (SCC) [1216]. In addition to keratin, SCC is further marked by the presence of keratin pearls and intercellular bridges [13].…”
Section: Discussionmentioning
confidence: 99%
“…Most reported cases of epithelioid trophoblastic tumor have solitary nodules with a sharp tumor border growing in an expansive fashion, invading the cervix or myometrium deeply, which is consistent with our ultrasound findings (Figure 2). In contrast, placental‐site trophoblastic tumor shows infiltrating growth penetrating between muscle fibers8–11. Ultrasonography may be helpful for differentiating between these two types of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Generally the behavior of epithelioid trophoblastic tumor is similar to that of placental‐site trophoblastic tumor, and both of them usually behave in a benign fashion, but metastasis and death occur in about 25% and 10% of cases, respectively3. Epithelioid trophoblastic tumor, like placental‐site trophoblastic tumor, may be unresponsive to the chemotherapeutic agents used in the treatment of other types of gestational trophoblastic disease and the recommended primary treatment is surgical intervention8, 11, 12.…”
Section: Discussionmentioning
confidence: 99%